2017
DOI: 10.1002/brb3.698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levodopa/carbidopa intestinal gel versus oral levodopa/carbidopa on B vitamin levels and neuropathy

Abstract: ObjectivesTo determine the possible interactions between levodopa therapy and plasma levels of B vitamins in patients with advanced idiopathic Parkinson's disease (IPD) in the context of either oral levodopa therapy or levodopa/carbidopa intestinal gel (LCIG). Secondly, to determine the prevalence of neuropathy and its relation to plasma levels of B vitamins and homocysteine.MethodsMedication doses, neurographies, and serum levels of pyridoxine, cobalamin, folate, and homocysteine of eight LCIG and 13 orally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 33 publications
3
49
1
1
Order By: Relevance
“…The association between PNP and oral l ‐dopa was evaluated in 19 studies, , including a total of 1,137 patients. A total of 353 PNPs were described, with a large predominance of slowly progressive axonal neuropathy selectively involving the sensory fibers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between PNP and oral l ‐dopa was evaluated in 19 studies, , including a total of 1,137 patients. A total of 353 PNPs were described, with a large predominance of slowly progressive axonal neuropathy selectively involving the sensory fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The association between PNP and l ‐dopa dosage was evaluated in 16 studies: 12 found an association between PNP and higher doses of l ‐dopa, whereas four showed negative results . Three studies did not provide any measures of association between PNP and l ‐dopa dosage …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolism of levodopa consumes pyridoxine, folate, and cobalamin. Some studies have provided evidence supporting that levodopa neuropathy is dose‐dependent, with higher doses causing more severe axonal loss and widespread damage . With doses of levodopa 2000 mg per day or higher, nearly all patients develop pyridoxine deficiency regardless of the route of administration .…”
Section: Pyridoxine (Vitamin B6)mentioning
confidence: 99%
“…New data have found a higher prevalence of polyneuropathy in PD patients than in age-matched controls (4)(5)(6)(7). Peripheral nerve fiber impairment in PD can take the form of large fiber neuropathy (PN) in L-Dopa treated patients (5)(6)(7)(8)(9)(10)(11)(12) or small fiber neuropathy (SFN) in all PD patients (13)(14)(15). A se-ries of data consider PN to be secondary to L-Dopa intake that determines the accumulation of homocysteine and methylmalonic acid, and cyanocobalamin, pyridoxine or folate plasma deficits (4,(6)(7)(8)11,(16)(17)(18).…”
mentioning
confidence: 99%